2023
DOI: 10.1136/bmjgh-2022-011338
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the African cancer research ecosystem: tackling disparities

Abstract: Disparities in cancer research persist around the world. This is especially true in global health research, where high-income countries (HICs) continue to set global health priorities further creating several imbalances in how research is conducted in low and middle-income countries (LMICs). Cancer research disparities in Africa can be attributed to a vicious cycle of challenges in the research ecosystem ranging from who funds research, where research is conducted, who conducts it, what type of research is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The context of the reported studies—including the funding sources, where research is done, by whom, and where research is published—is important for understanding the global health research ecosystem within which the purpose and scope of research is formulated, [ 37 ] A majority of papers reported on studies carried out within the context of a trial or intervention, suggesting that qualitative research has been brought in primarily to answer questions about implementation-related variables, e.g., feasibility and acceptability, and potentially omitting critical questions that social scientists might pose, such as those pertaining to the broader structural conditions in which POCTs are prioritised, funded, developed and deployed, or the ways in which POCTs reconfigure power relationships in medicine (see e.g., [ 38 42 ]). Ethnographic methods are especially well-suited to unearthing these social and political dimensions of global health technologies [ 9 , 43 – 45 ] and have been shown to be essential to better understand the lived experience and everyday workings of health systems and technologies in real-world settings (e.g., [ 2 , 10 12 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The context of the reported studies—including the funding sources, where research is done, by whom, and where research is published—is important for understanding the global health research ecosystem within which the purpose and scope of research is formulated, [ 37 ] A majority of papers reported on studies carried out within the context of a trial or intervention, suggesting that qualitative research has been brought in primarily to answer questions about implementation-related variables, e.g., feasibility and acceptability, and potentially omitting critical questions that social scientists might pose, such as those pertaining to the broader structural conditions in which POCTs are prioritised, funded, developed and deployed, or the ways in which POCTs reconfigure power relationships in medicine (see e.g., [ 38 42 ]). Ethnographic methods are especially well-suited to unearthing these social and political dimensions of global health technologies [ 9 , 43 – 45 ] and have been shown to be essential to better understand the lived experience and everyday workings of health systems and technologies in real-world settings (e.g., [ 2 , 10 12 ]).…”
Section: Discussionmentioning
confidence: 99%
“…23 It has been noted that the African Union in 2007 committed to investing at least 1% of gross domestic product (GDP) in research and development but 15 years later, no country had achieved that goal. 24 Available data shows that sub-Saharan Africa invests 0.44% of GDP in research and development compared to 3.32% in north America, 2.28% in the European Union and global average of 2.71% (Table 4). 25…”
Section: Impactmentioning
confidence: 99%
“…One way of dealing with the uneven playing field is to design new collaborations between African researchers and colleagues in highincome countries. Maintaining equity is difficult, given the disparities in resources, says Rubagumya, who is lead author of a 2023 study 4 that describes a "vicious cycle of challenges in the research ecosystem" that maintains an imbalance towards high-income nations.…”
Section: Breaking the Cyclementioning
confidence: 99%